TECHNOLOGY OF IMPLEMENTATION OF INDIVIDUALIZATION OF PROFESSIONAL FOCUSED STUDENT LEARNING IN CLASSES FOREIGN LANGUAGE (Pedagogy of Higher and Secondary Education, 2003)
The article is devoted to the problem of individualization of professionaloriented learning. The author considers' the implementation technology of students’ teaching individualization as means of professional intention of foreign languages learning at non-linguistic faculties.